Association of the Pattern and Quality of Sleep with Consumption of Stimulant Beverages, Cigarette and Alcohol among Medical Students - Bogati, Sunil; Singh, Tulika; Paudel, Sagar; Adhikari, Baikuntha; Baral, Dharanidhar (Journal of Nepal Health Research Council, 2020)
Background: Sleep is important in maintenance of proper functioning of both mental and physical functions of human body. Studies have shown there is impact on the sleep parameters with the use of caffeine, cigarette and alcohol. As there is little availability of similar studies here in Nepal, we made an attempt to know the relation of consumption of such substances with the sleep quality and sleep parameters as per Pittsburgh Sleep Quality Index scale. Methods: A cross sectional study was conducted among the undergraduate students at BP Koirala Institute of Health Sciences, Dharan. Students were asked to complete a self- administered questionnaire to give information about demographic variables and habit of consumption of caffeinated beverages, cigarette and alcohol. The Pittsburgh Sleep Quality Index was utilized after the permission from authority to evaluate sleep quality. Results: Out of 350, almost half of the students (44.6%) had poor sleep quality. 40.8% students reported sleeping six hours or less per night and 10.1% used medications to sleep. 96% reported consuming caffeinated beverages, 20% consumed cigarettes and 38.3% consumed alcoholic beverages. There was significant association of poor sleep quality with the increased consumption caffeine, cigarette and alcohol (p<0.05). Conclusions: Poor sleep is prevalent among the undergraduate students of B P Koirala Institute of Health Sciences and the consumption of caffeine, cigarette and alcohol is associated with increment in poor sleep quality among them. Keywords: Caffeinated beverages; pittsburgh sleep quality index